Pengaruh Penggunaan Media Gambar terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas VIII SMP Negeri 18 Makassar - Asis, Nurasia; Hamsa, Akmal; Haliq, Abdul (PPJB-SIP (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya)., 2025)
This research aims to (1) describe the expository text writing skills of Class VIII students at SMP Negeri 18 Makassar; (2) describe the expository text writing skills of Class VIII students at SMP Negeri 18 Makassar after using image media; (3) describe the influence of using image media on the expository text writing skills of Class VIII students at SMP Negeri 18 Makassar. The type of research used is quantitative research using the Pre-Experimental method. The data collection technique in this research is a task that is divided into Pretest and Posttest. The population of this research was all Class VIII students at SMP Negeri 18 Makassar consisting of 10 classes with a total of 297 students and the sample was taken using a purposive sampling technique, so the researcher determined the research sample set at Class VIII.3 totaling 30 students. The data analysis used in this research is descriptive statistical analysis and inferential statistical analysis. The results of the research revealed that the expository text writing skills of Class VIII students at SMP Negeri 18 Makassar before using image media obtained an average score of 62.73 in the less skilled category. The results of the expository text writing skills of Class VIII students at SMP Negeri 18 Makassar after using image media obtained an average score of 83.76 in the skilled category. Based on the Statistical Test Output in the simple regression test above, it is known that the value of Asymp. Sig (2-tailed) = 0.001 from 29 students. The value 0.001 < 0.05 means it can be stated that H0 is rejected and H1 is accepted. Thus, it can be concluded that there is an influence of the use of image media on writing exposition texts for Class VIII students at SMP Negeri 18 Makassar.